Kemampuan Siswa dalam Memahami Bahan Ajar Sejarah Perjuangan Rakyat Bengkulu pada Aspek Kognitif dan Aspek Afektif pada Mata Pelajaran Muatan Lokal di Kelas V Sekolah Dasar Negeri 49 Kota Bengkulu - Afrianti, Titin; Wurdjinem, Wurdjinem; Kustianti, Sri Ken (UNIB Press, 2018)
This study aimed to describe the ability of students to understand the teaching materials on the history of the struggle of the people of Bengkulu local content subjects at three aspects of the history of the learning outcomes of academic skills (cognitive), awareness of history (affective), nationalism (affective). This type of research is descriptive quantitative research with descriptive methods and techniques percentage. The subjects were students of class VA amounting to 23 students. The research instrument used is a matter of objective test sheet form and the sheet observation / observasi.teknik data analysis by scoring on a multiple choice test and scoring on a sheet of observation / observation later described. From the research that VA grade students of State Elementary School 49 Bengkulu City was able to understand the history of the struggle of people teaching materials Bengkulu with an average of 68.11% in understanding the teaching materials on the history of the struggle of the people of Bengkulu local content subjects. However, if viewed from the completeness graders said VA has not been completed, because based on the assessment of students declared complete benchmark reference when getting values over 65 as much as 75-80%. It can be concluded that based on the calculation that has been obtained in the aspect of academic skills (cognitive) as many as 12 students (52.17%) were able to understand the history of the struggle of the people teaching materials Bengkulu, A total of 16 students (69.56%) had a history conscious attitude. And to nationalism as many as 19 students (82.60%) were able to have an attitude of nationalism.